A Profile Of Anganwadi Workers In Jawan Block Of District Aligarh, Uttar Pradesh - Khan Z; Hasan J (Wolters Kluwer Medknow Publications, 1992)
One hundred and ten anganwadi workers in Jawan block of district Aligarh were contacted and interviewed. Their socio- cultural characteristics as well as their knowledge and attitude towards common health problems were studies.